INTENSITAS NYERI PADA ARTHRITIS: TINJAUAN SISTEMIK LITERATUR - Birman, Yuliza; Nirwana, Putri Sinthya; Haiga, Yuri (Nusantara Hasana Journal, 2025)
Arthritis is an inflammation of the joints characterized by pain as the main symptom. The most common types are osteoarthritis (OA), rheumatoid arthritis (RA), and gout arthritis (GA). One way to assess the intensity of pain is by using the Visual Analogue Scale (VAS). This study is a systematic literature review aimed at reviewing the differences in pain intensity among types of arthritis based on previous studies. The results show that pain intensity in RA is classified as mild to moderate (VAS ±3.4), OA is moderate to severe (VAS 4–6), and GA is severe during the acute phase (VAS 7–9). Factors such as age, gender, and psychological conditions also influence pain perception. Understanding this is essential to support appropriate management and improve the quality of life for patients.